A Qualitative Examination of Bisexual+ Identity Invalidation and Its Consequences for Wellbeing, Identity, and Relationships. Issue 4 (2nd October 2019) - Feinstein, Brian A.; Franco, Marisa; Henderson, Regine; Collins, Laniqua Kemecee; Davari, Jaleh
Abstract: Bisexual+ people (i.e., those attracted to people of more than one gender/sex) face unique stressors related to their sexual orientation, but identity invalidation (experiences in which others deny, negate, or refuse to accept an individual's identity) has received limited empirical attention. As such, the goals of the current study were to examine manifestations of bi+ identity invalidation and their consequences for wellbeing, identity, and relationships. Fifty-two bi+ participants completed a qualitative survey that asked them to describe their most stressful experience of identity invalidation. Three coders analyzed the data using a consensual qualitative research approach, and the coding scheme was confirmed by two auditors. Most participants (85%) had experienced identity invalidation. They described five perceived reasons: (1) others did not understand or accept bi+ identities; (2) the gender of their partner did not fit with others' beliefs about bi+ identities; (3) others believed they were confused; (4) others believed they were "faking" it; and (5) others rejected bi+ identities for religious reasons. Participants described consequences of identity invalidation including negative emotions, identity-related challenges, and relational difficulties. These findings suggest that identity invalidation is a common experience among bi+ people and it may be an important intervention target.